Anisotropic Particle Assemblies : Synthesis, Assembly, Modeling, and Applications - Wu, Ning; Lee, Daeyeon; Striolo, Alberto (Elsevier, 2018)
"Anisotropic Particle Assemblies: Synthesis, Assembly, Modeling, and Applications covers the synthesis, assembly, modeling, and applications of various types of anisotropic particles. Topics such as chemical synthesis and scalable fabrication of colloidal molecules, molecular mimetic self-assembly, directed assembly under external fields, theoretical and numerical multi-scale modeling, anisotropic materials with novel interfacial properties, and the applications of these topics in renewable energy, intelligent micro-machines, and biomedical fields are discussed in depth. Contributors to this book are internationally known experts who have been actively studying each of these subfields for many years. This book is an invaluable reference for researchers and chemical engineers who are working at the intersection of physics, chemistry, chemical engineering, and materials science and engineering. It educates students, trains the next generation of researchers, and stimulates continuous development in this rapidly emerging area for new materials and innovative technologies. Provides comprehensive coverage on new developments in anisotropic particlesFeatures chapters written by emerging and leading experts in each of the subfieldsContains information that will appeal to a broad spectrum of professionals, including but not limited to chemical engineers, chemists, physicists, and materials scientists and engineersServes as both a reference book for researchers and a textbook for graduate students"--